2023
DOI: 10.1029/2022jb025135
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Carbonate‐Bearing Silicate Sediments in the Sources of Circum‐Mediterranean K‐Rich Lavas: Evidence From Mg‐Zn Isotopic Decoupling

Abstract: The solid Earth contains more carbon than the entire surface reservoir (ocean, atmosphere, and biosphere) in terms of mass: over 90% of carbon is located in the crust, mantle, and core (Dasgupta & Hirschmann, 2010;Wood, 1993). Carbon is released from the Earth's interior mainly in the form of carbon dioxide (CO 2 ) by degassing from volcanoes (up to 90%) and metamorphic reactions (≈10%; Mason et al., 2017). The flux of CO 2 released from oceanic volcanism (mid-ocean ridges and ocean islands) is ∼29-154 Megaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Recently, Shu et al. (2023) revealed that recycled carbonate‐bearing silicate sediments could induce Mg‐Zn isotopic decoupling in mantle‐derived magmas, especially in the case of low carbonate fractions in the sediments. Continental margin sediments (0.07‰ ± 0.11‰; Little et al., 2016) have a significantly lighter Zn isotopic signature than normal mantle, and these sediments can be incorporated into the continental mantle through subduction erosion (Straub et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shu et al. (2023) revealed that recycled carbonate‐bearing silicate sediments could induce Mg‐Zn isotopic decoupling in mantle‐derived magmas, especially in the case of low carbonate fractions in the sediments. Continental margin sediments (0.07‰ ± 0.11‰; Little et al., 2016) have a significantly lighter Zn isotopic signature than normal mantle, and these sediments can be incorporated into the continental mantle through subduction erosion (Straub et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, considering that mantle partial melting would slightly enrich the melt with heavy Zn isotopic compositions (e.g., Sossi et al, 2018;Wang et al, 2017), the mantle source of parental melts for clinopyroxenites should have a lighter Zn isotopic composition (<0.04‰). Recently, Shu et al (2023) revealed that recycled carbonate-bearing silicate sediments could induce Mg-Zn isotopic decoupling in mantle-derived magmas, especially in the case of low carbonate fractions in the sediments. Continental margin sediments (0.07‰ ± 0.11‰; Little et al, 2016) have a significantly lighter Zn isotopic signature than normal mantle, and these sediments can be incorporated into the continental mantle through subduction erosion (Straub et al, 2020).…”
Section: Mantle Source Heterogeneity and Later-stage Melt/fluid Metas...mentioning
confidence: 99%
“…This is also in accordance with the recent studies investigating the fate of the CO 2 in the upper mantle, underscoring that the Tethyan subduction might have transported a much larger amount of CO 2 than previously assumed 71,76,81 . Moreover, it is also recently proposed that the recycled carbonate sediments are responsible for low δ 26 Mg and high δ 66 Zn signatures observed in the Mediterranean lamproites defining so-called "Mg-Zn isotopic decoupling" 82 .…”
Section: Discussionmentioning
confidence: 99%
“…Zn-Mg isotope compositions in other circum-Mediterranean magmas suggests the recycling of marls (Shu et al, 2023). In the area, high precision HFSE data are available for the Rhodopes (Bulgaria) and Santorini (Kirchenbaur and Münker, 2015).…”
Section: Comparison With Other Potassic and Ultrapotassic Rocks In Th...mentioning
confidence: 99%